Experimental Study of Hydraulically Expanded Tube-to-Tubesheet Joints for Shell-and-Tube Heat Exchangers. (2015) - Ma, H.; Yu, H.J.; Qian, C.F.; Liu, Z.S.; Zhou, J.X.
Abstract: In this paper, the hydraulically expanded tube-to-tube sheet joints for shell-and-tube heat exchangers made of three sets of commonly used tube and tunesheet materials i.e. 10# for tube and 16Mn for tubesheet, S30408 stainless steel for both tube and tubesheet, and S32168 stainless steel for the both were experimentally studied with the concentration on the relations between the tube expanding percentage, expansion pressure, pull-out force and push-out force. The tube expanding percentages within the ranges of expanding pressure from 160 MPa to 300 MPa for different materials joints were obtained. Both pull-out and push-out tests were carried out for each joint. Results show that the tube expanding percentage almost increases linearly with increasing the expansion pressures. Pull-out force is less than the push-out force and both of them increase with increasing expansion pressures. However unlimited increase of the tube expanding percentage cannot always enhance the pull-out strength of the joints because of "over-expansion". Finally, to facilitate the application, the relationships between the tube expanding percentage and expanding pressure are given, and also provided are the equations of the relationship between the pull-out force and the tube expanding percentage.